'Empowering clinicians in smaller sites': A qualitative study of clinician's experiences with a rural Virtual Paediatric Feeding Clinic. (7th September 2021) - Luscombe, Georgina M.; Hawthorn, Juliet; Wu, Alison; Green, Belinda; Munro, Alice
Abstract: Objective: To explore the experiences of 'spoke site' allied health and child and family health clinicians in the provision of care through a pilot 'hub and spoke' model Virtual Paediatric Feeding Clinic (VPFC) outreach service. Design: The study was qualitative, with data from virtual interview transcripts analysed using thematic analysis. Setting: Orange Health Service ('hub site') and seven community health centres within the Western NSW Local Health District ('spoke sites'). Participants: Nine 'spoke site' clinicians (from dietetics, speech pathology, occupational therapy and child and family health nursing), who had participated in the pilot clinic. Interventions: Participants took part in a semi‐structured interview with a member of the research team. Main outcome measures: Spoke site clinicians experiences and perceptions of the VPFC. Results: Four key themes emerged: (1) impact of the VPFC on 'spoke site' clinicians, (2) benefits for clients and families, (3) perceptions of the virtual model of care and (4) VPFC service challenges. Conclusion: The expansion of an existing interdisciplinary Paediatric Feeding Clinic into a virtual service demonstrates the use of technology to bridge a gap in healthcare. Clinicians reported benefits not only for families, but for their own knowledge and confidence in provision of care and reduced professional isolation through connection with discipline‐specific colleagues.